Challenges and Overview of License Plate Character Segmentation - Sharma, Pankaj; sing, Jai karan; sing, Jai karan (International Journal of Computer Sciences and Engineering, 2015)
License plate identification or recognition has become an important part of vehicle surveillance systems. This paper, reviews the basic methodologies used for identification of vehicle number plates. Over main concern in this paper is to review the edge based methods. Since edge detection based methods are simple and thus widely used for real time recognition of the license number plate Paper also briefly describes the various problems and shortcomings of the existing methods. Paper also addresses the problem of automatic number plate detection. Paper also reviews the various color spaces used for number plate identification. The basic results of the various edge detectors are also presented for different input images.